The Use of Modified Composite Zeolite as A Novel Approach to Dental Hygiene Formulation - Rahman, Sumaita (2024)
A Master of Science thesis in Chemical Engineering by Sumaita Rahman entitled, “The Use of Modified Composite Zeolite as A Novel Approach to Dental Hygiene Formulation”, submitted in May 2024. Thesis advisor is Dr. Taleb Ibrahim and thesis co-advisor is Dr. Sarah Dalibalta. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).